THE ROLE OF ZINC, SODIUM AND POTASSIUM INTAKE ON BLOOD LIPID PROFILES - Retiaty, Fifi; Palupi, Nurheni Sri; Ernawati, Fitrah; Andarwulan, Nuri (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2025)
Blood lipid parameters are influenced by nutrient intake, both macronutrients and micronutrients. This study aims to analyze the relationship between zinc (Zn), sodium (Na), and potassium (K) with lipid profiles (total cholesterol, triglycerides (TG), low-density lipoprotein (LDL), and high-density lipoprotein (HDL). The study design was cross-sectional using secondary data from the 2017 Non-Communicable Disease Risk Factor Cohort Study which took 3,507 samples from a population of 5,329 respondents with a purposive sampling technique. The data analyzed included sociodemographic characteristics data, lipid profile data, and 1x24-hour recall consumption data. Data processing used logistic regression analysis and correlation with a 95% confidence level. The study results showed that gender, age, education level, and marital status had a significant relationship with lipid profiles. The results of this study were micronutrients and lipid profiles showed a significant negative relationship between sodium, potassium, and zinc with cholesterol and a significant negative relationship between potassium and LDL. This study concludes that the greater risk of dyslipidemia is female gender, increasing age, low education level, and marital status with divorced category. Sodium, potassium, and zinc have a relationship with the occurrence of dyslipidemia. Further research is needed, and a more comprehensive study is required to analyze the relationship between micronutrients and dyslipidemia.